Two newly recorded species of Aspidistra (Asparagaceae) for the flora of China: A. obliqua and A. triradiata - Nuraliev, Maxim S.; Romanov, Mikhail S.; Drokina, Victoria G.; Fu, Long-Fei; Vislobokov, Nikolay A. (Phytotaxa, 2023)
Findings of two species of Aspidistra, i.e. A. obliqua and A. triradiata, are reported from Guangxi Zhuang Autonomous Region, representing the first documented records of these species from China. Both species were earlier considered to be endemic to northern Vietnam. Analytical photographs of the studied plants in living state are provided. Morphological variation of the species under study is briefly discussed. Geographical distribution of the two species is summarized and depicted on a map.